The Great Depression: 1929-1939 - Axelrod, Paul (Labour / Le Travail, 1992)
The article reviews the book, "The Great Depression: 1929-1939," by Pierre Berton.
Keywords: BERTON, Pierre, 1920-2004; BOOKS -- Reviews; DEPRESSIONS -- 1929; GREAT Depression 1929-1939, The (Book); Nonfiction